Business Strategy of Renewable Energy Project to Enhance Revenue in Business Transition - Theodorus Tio Wibowo; Sylviana Maya Damayanti; Uke Marius Siahaan (Green Publisher Indonesia, 2026)
This research is motivated by the increasing urgency of the global energy transition to reduce carbon emissions and expand the use of renewable energy sources. Indonesia’s energy sector is still heavily dominated by fossil fuels, particularly coal, which contributes more than 60% of the country’s electricity generation. This condition highlights the need for business strategies that can support the development of renewable energy while maintaining sustainable corporate revenue during the transition process. Solar energy through Solar Photovoltaic (PV) technology has emerged as a promising alternative due to its rapidly declining technology costs and relatively faster project implementation compared to other renewable energy sources. This study aims to analyze the economic feasibility and business strategies of Solar PV projects in enhancing company revenue during the energy transition, particularly through Engineering, Procurement, and Construction (EPC) and Build-Own-Operate-Transfer (BOOT) project schemes. The research employs a quantitative approach using financial feasibility analysis methods, including Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PBP). The analysis is further supported by sensitivity analysis and the US Index framework to evaluate the most appropriate financing structure. The results show that the Solar PV project in West Java is financially feasible, with an IRR of 20%, which is higher than the Weighted Average Cost of Capital (WACC) of 7.38%, and a payback period of approximately 4–5 years. Furthermore, financing through international bank loans provides the most optimal financial performance, generating the highest NPV and the lowest cost of capital.